The role and place of transanal endoscopic resections in rectal cancer - R. P. Nikitenko; V. M. Zaporozhan; K. O. Vorotyntseva; Ye. A. Koichev (Zaporožskij Medicinskij Žurnal)
The aim of the work is to improve the algorithm of intraoperative diagnosis of rectal cancer metastasis in order to optimize surgical intervention and reduce the number of intraoperative and postoperative complications.